Receptors That Inhibit Macrophage Activation: Mechanisms and Signals of Regulation and Tolerance - Ranferi Ocaña-Guzman; Luis Vázquez-Bolaños; Isabel Sada-Ovalle (Journal of Immunology Research)
A variety of receptors perform the function of attenuating or inhibiting activation of cells in which they are expressed. Examples of these kinds of receptors include TIM-3 and PD-1, among others that have been widely studied in cells of lymphoid origin and, though to a lesser degree, in other cell lines. Today, several studies describe the function of these molecules as part of the diverse mechanisms of immune tolerance that exist in the immune system. This review analyzes the function of some of these proteins in monocytes and macrophages and as well as their participation as inhibitory molecules or elements of immunological tolerance that also act in innate defense mechanisms. We chose the receptors TIM-3, PD-1, CD32b, and CD200R because these molecules have distinct functional characteristics that provide examples of the different regulating mechanisms in monocytes and macrophages.